Dron’t Stop Me Now: Prioritizing Drone Journalism in Commercial Drone Regulation - Fischer, David A (The Columbia Journal of Law & the Arts, 2019)
New technologies that simplify lives and improve our understanding of the world around us inevitably pose new, difficult legal questions. This maxim is true for commercial drones. The recent proliferation of these devices creates a multitude of opportunities for commercial use. To borrow a phrase from Justice Robert H. Jackson, the ability of drones to navigate the sky like “vagrant clouds”4 also means that these devices pose significant regulatory challenges for federal, state, and local governments. Governments attempting to address the safety, privacy, and region- specific concerns raised by increased commercial drone use must also consider the concomitant burdens placed on commercial drone use. This Note proceeds in four parts. Part I highlights novel journalistic uses of drones for content production and investigative reporting and discusses the pitfalls of under- or overregulating commercial drones. Part II details the current state of federal, state, and local regulation of commercial drone use. Keeping in mind potential changes that may result to the FAA’s Part 107 commercial drone regulations from the FAA Reauthorization Act of 2018, this Note considers the FAA’s current regulations as a baseline for whether new regulations would help or hinder drone journalism. The state and local picture is more intricate, and this Note discusses those regulations in three parts: safety regulations, privacy regulations, and region-specific regulations. Part III discusses federal safety regulations and the First Amendment and proposes simplifying the regulatory picture by preempting most state and local safety regulations. Part IV examines whether the federal regulatory scheme preempts state and local privacy regulations and common law torts, the application of those common law torts, and First Amendment limitations on state and local privacy regulations. The Conclusion details how an aspiring drone journalist would experience the regulatory scheme proposed herein.